Cultivation of a high value crop â€“ sweet corn (Zea mays Linn.) in poplar based agroforestry - Dhiman, R.C.; Gandhi, J.N. (Indian Journal of Agroforestry, 2020)
The results of four field trials on growing sweet corn (Zea mays Linn.) under poplar plantations (clone WSL 39)Â  of five different ages are presented. The age of poplar plantations was 2, 14, 26, 38 and 50 months when sweet corn was sown and 6, 18, 30, 42 and 54 months respectively when it was harvested. The intercrop was sown during April and harvested during August of 2006, 2007, 2008 and 2009.The results of sweet corn yield grown under poplar trees were also compared with that grown in open conditions. Results revealed that the age of poplar trees had significant influence on yield of sweet corn cobs and fodder. Tree height and diameter increment in 14 months old plantations was significantly higher than the other aged plantations. The economical analysis of growing sweet corn under poplar plantations indicated positive cash flow to the growers till the stage of 2 years age of trees and decreased thereafter.